1981
DOI: 10.1099/0022-1317-55-1-179
|View full text |Cite
|
Sign up to set email alerts
|

One Functional Copy of the Long Terminal Repeat Gene Specifying the Immediate-early Polypeptide IE 110 Suffices for a Productive Infection of Human Foetal Lung Cells by Herpes Simplex Virus

Abstract: SUMMARYThe HSV-1/HSV-2 intertypic recombinant Bxl (28-1) is heterotypic for the repeat sequences flanking the long unique region of the genome (IR L and TR L) and expresses both the immediate-early polypeptide IE 110 of HSV-1 and its functionally equivalent polypeptide IE 118 of HSV-2. The genome structures of five subclones of this recombinant and the immediate-early polypeptides they induce have been analysed. Subclone 14 lacked most of the IR r sequence, including the region from which part of the mRNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…Genomic deletions occurred in stocks of virus which had been neither treated with restriction endonucleases nor transfected. The high frequency of occurrence of long repeat deletions in strain HG52 firmly ruled out the suggestion that such deletions were a consequence of heterotypic repetitive regions (Davison et al, 1981). We feel it is more probable that deletions originate from distinct regions of instability in the DNA, for example banks of tandemly reiterated short sequences like those found in the long repeat near the UL/IRL junction, in the middle of IRL, near the IRL/IRs joint and in Us of personal communication).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Genomic deletions occurred in stocks of virus which had been neither treated with restriction endonucleases nor transfected. The high frequency of occurrence of long repeat deletions in strain HG52 firmly ruled out the suggestion that such deletions were a consequence of heterotypic repetitive regions (Davison et al, 1981). We feel it is more probable that deletions originate from distinct regions of instability in the DNA, for example banks of tandemly reiterated short sequences like those found in the long repeat near the UL/IRL junction, in the middle of IRL, near the IRL/IRs joint and in Us of personal communication).…”
Section: Discussionmentioning
confidence: 78%
“…Other strains of HSV-2 exhibit simdar deletions showing that the HG52 strain is not exceptional. Deletions in the long repeat had been observed previously in intertypic reeombinants when Davison et al (1981) suggested that they probably arose as a consequence of heterotypic repetitive regions. Our observations show that this could not be the explanation but that deletions within one copy of the long repeats of the HG52 genome are relatively common.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…There is no published information on the extent of unique-sequence transcription during productive infections with HVS. The possibility that all the functions required for a productive infection with HVS may be encoded within a small fraction of the unique genome sequences cannot be dismissed a priori, given such familiar precedents as bacteriophage 2 and examples of duplicated and dispensable functions in the genome of herpes simplex virus (Davison et al, 1981 ;Post & Roizman, 1981). However, such a situation would be unexpected and the persistence of host protein synthesis may have prevented the detection of a significant number of virus-specified early gene products.…”
Section: Demonstration O F a N Electrophoretically Distinct Nuclear Pmentioning
confidence: 99%
“…Banks of tandem repeats are believed to be responsible for the variation in size of certain restriction fragments, which is seen between strains and between single plaque isolates within a strain (Lonsdale et al, 1980). Variation is also found in the size of the terminal and joint fragments which contain the 'a' sequence but this is due to variability in the number of 'a' sequences present (Davison & Wilkie, 1981).…”
Section: Introductionmentioning
confidence: 99%